Biopotensi Bakteri Entomopatogen Isolat Lokal sebagai Pengendali Hayati Larva Helicoverpa armigera (Hübner) - Suhartono Suhartono; Yekki Yasmin; Nur Azizah (Institut Pertanian Bogor, 2022)
The use of insecticides in the intensive control of Helicoverpa armigera caterpillars increases the environmental deterioration, the natural enemies, and threatening the user's health. The study aims to isolate, characterize, and determine the biological potential of local isolates of entomopathogen bacteria as the biological controlling agent on H. armigera larvae. Bacterial isolation was performed using a serial dilution followed by bacterial macroscopic and microscopic characterizations. A total of eight entomopathogen bacterial isolates were successfully obtained from this study, namely IBE 01, IBE 02, IBE 03, IBE 04, IBE 05, IBE 06, IBE 07, and IBE 08 with diverse morphological characters. The dead larvae generally showed soft, blackish/brownish, smelly, and watery characteristics. Characteristics due to infection with entomopathogen IBE 04 bacteria show the body of larvae that are soft, reddish, and smelly. The treatment of IBE 07 isolates results in the body of the dead larvae being easily ruptured, reddish, and smelly. The percentage of IBE on the mortality of H. armigera larvae is > 50%. The isolates with the highest percentage of killing the larvae were IBE 04 and IBE 07, at 94% and 88%, respectively. Keywords: biocontrol, larvicide, entomopathogenic bacteria, Helicoverpa armigera